2022
DOI: 10.3892/etm.2022.11630
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone‑induced autophagy mitigates doxorubicin‑induced H9c2 cell apoptosis

Abstract: Doxorubicin (Dox)-induced myocardiopathy is a massive obstacle in administering chemotherapeutic drugs in cancer patients. In the present study, the effects of thymoquinone (TQ) on Dox-induced cardiotoxicity were investigated in vitro. H9c2 cardiomyocytes were pre-treated with TQ followed by Dox, and cell viability and cell death were subsequently measured. Flow cytometry was conducted to evaluate the apoptosis of H9c2 cells. Autophagy was assessed by immunofluorescence LC3 staining. Western blot analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Also, other studies have shown the protective effects of TMQ in reducing cardiotoxicity (Karabulut et al, 2021; Öztürk et al, 2020). In the study by Liu et al, treatment with TMQ significantly reduced cardiotoxicity caused by doxorubicin (Liu & Zhao, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Also, other studies have shown the protective effects of TMQ in reducing cardiotoxicity (Karabulut et al, 2021; Öztürk et al, 2020). In the study by Liu et al, treatment with TMQ significantly reduced cardiotoxicity caused by doxorubicin (Liu & Zhao, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As light chain 3 (LC3)‐II serves as a widely accepted marker for autophagosomes and relatively specifically related to autophagosomes and autolysosomes, the quantification of LC3‐positive puncta is deemed gold‐standard for determining autophagosome numbers in cells 37 . Immunofluorescence assay was performed as reported 38 . HKFs were fixed for 15 min with 4% paraformaldehyde, rinsed with NaCl/Pi, permeabilized with 0.2% Triton X‐100, and incubated at 4°C with LC3B primary rabbit antibody (1:200, #3868, CST, Danvers, MA, USA) overnight.…”
Section: Methodsmentioning
confidence: 99%
“…37 Immunofluorescence assay was performed as reported. 38 HKFs were fixed for 15 min with 4% paraformaldehyde, rinsed with NaCl/Pi, permeabilized with 0.2% Triton X-100, and incubated at 4°C with LC3B primary rabbit antibody (1:200, #3868, CST, Danvers, MA, USA) overnight. Next, cells were probed with Alexa 594-conjugated goat anti-rabbit secondary antibody (1:200, #8889, CST) at 37°C for 1 h. The images were taken captured using a fluorescence microscope (Carl Zeiss Meditec AG).…”
Section: Immunofluorescencementioning
confidence: 99%